2011
DOI: 10.1186/1471-2202-12-8
|View full text |Cite
|
Sign up to set email alerts
|

Microarray-based gene expression profiles of silkworm brains

Abstract: BackgroundMolecular genetic studies of Bombyx mori have led to profound advances in our understanding of the regulation of development. Bombyx mori brain, as a main endocrine organ, plays important regulatory roles in various biological processes. Microarray technology will allow the genome-wide analysis of gene expression patterns in silkworm brains.ResultsWe reported microarray-based gene expression profiles in silkworm brains at four stages including V7, P1, P3 and P5. A total of 4,550 genes were transcribe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
3
6
0
Order By: Relevance
“…Neuropeptides are a kind of bioactive substance that exist in nervous tissue and play key roles in regulating the function of the nervous system. It has been reported that 51 neuropeptides are expressed in the silkworm brain, such as neuropeptide F1, short neuropeptide F, bombyxin, PTTH, corazonin, and so on . PTTH is a homodimeric glycoprotein; our qRT-PCR results showed that its coding gene was highly expressed at wandering stage (Figure F), which was consistent with previous results .…”
Section: Discussionsupporting
confidence: 92%
“…Neuropeptides are a kind of bioactive substance that exist in nervous tissue and play key roles in regulating the function of the nervous system. It has been reported that 51 neuropeptides are expressed in the silkworm brain, such as neuropeptide F1, short neuropeptide F, bombyxin, PTTH, corazonin, and so on . PTTH is a homodimeric glycoprotein; our qRT-PCR results showed that its coding gene was highly expressed at wandering stage (Figure F), which was consistent with previous results .…”
Section: Discussionsupporting
confidence: 92%
“…Totally, 15 neuropeptides and 66 neuropeptide receptors were identified from head of adult P. flammans , which was different with other lepidopteran species 44 47 and should partly be relevant with their differences in sample physiological status. For example, in B. mori , 32 neuropeptide genes and 6 neuropeptide-like precursor genes were identified from larval and pupal brain 45 . In C. suppressalis , 43 neuropeptide precursors and 51 putative neuropeptide G protein-coupled receptors were identified the fifth instar larval central nervous system including brain, suboeophageal ganglion, thoracic ganglion, and the abdominal ganglion 46 .…”
Section: Discussionmentioning
confidence: 99%
“…A burgeoning literature has linked changes in brain gene expression to changes in behavior in several species (20,21,23,24,39,45,74,79,91,100,103,117,122), but further work is needed.…”
Section: Is a Close Relationship Between Neurogenomic State And Behavmentioning
confidence: 99%